Functional Self-Limitation of State Authority - Makogon, Boris V.; Gogolev, Aleksej M.; Novikov, Andrey B.; Peterburgskiy, Andrey P.; Khakonova, Irina B. (Cuestiones Políticas, 2020)
Based on the analytical and synthesis study of a wide range of published documentary sources, the article presents the authors’ approach to the issue of self-restriction of state power. General theoretical aspects, historical and oriented to the current state of the problem were considered in order to analyze the self-limitation of the authority of the State in theory and in concrete reality. Methodologically, it is a study that uses in equal conditions the qualitative analysis of the systems and processes that emerge from the exercise of the authority of the State, with the hermeneutic reading of the legal doctrine that accounts for the matter. It is concluded that, in the considered context of the Russian Federation, the problem of the constant and continuous improvement of the system of separation of state power often seems to manifest itself satisfactorily. Theoretically, at first sight, once regulated, the corresponding system a priori acquires a constant and stable character, however, there is still a long way to go to achieve the foundation of a sustained dynamic of self-limitation and self-regulation of state power in in line with the principles of the rule of law.